Abnormal Expression of Centromere Protein U Is Associated with Hepatocellular Cancer Progression. (11th December 2021) - Yu, Yuanlin; Chen, Xiaopeng; Zhang, Weidong; Liu, Jun
Abstract : Background . Hepatocellular carcinoma (HCC) is one of the most common malignancies globally, but its molecular mechanism is unclear. Abnormal expression of centromere protein U (CENPU) is closely related to diverse human cancers. The purpose of this article was to evaluate the function and potential mechanisms of CENPU in HCC development. Methods . We performed bioinformatics analysis of The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), Gene Expression Profiling Interactive Analysis (GEPIA), and Kaplan-Meier plotter databases to investigate the clinical significance and prognostic value of CENPU in HCC. Western blotting and immunohistochemical staining were used to measure protein expression, while reverse transcription-quantitative polymerase chain reaction (qRT-PCR) was used to determine mRNA expression. Cell Counting Kit8 (CCK-8) and colony formation assays were conducted to examine cell proliferation. Transwell and wound healing assays were used to assess cell migration and invasion. Gene set enrichment analysis (GSEA) was used to explore the potential signaling pathways of CENPU involved in HCC. Results . High expression of CENPU in HCC was predicted by public database analysis and indicated a poor prognosis. CENPU expression was significantly higher in HCC tissues and cells than in normal tissues and cell. In vitro, CENPU promoted the proliferation, migration, and invasion of HCC cells. GSEA results indicated that CENPU was linked to the Notch signaling pathway, and our research supported this prediction. Conclusion . CENPU promotes the malignant biological process of HCC and may be a promising target for HCC treatment.